Knee Ultrasonography to Determine Risk for Noncontact Injuries in Collegiate American Football Players - Lewis, Ryan A.; Cook, Cristi R.; Smith, Patrick A.; Stannard, James P.; Sharp, Rex L.; Blecha, Kyle M.; Cook, James L. (The Journal of Knee Surgery, 2020)
Knee ultrasonography has been used effectively as a screening tool for determining risk for knee injuries in athletes. Ultrasonography may be a valuable screening tool for relative risk of noncontact knee injuries that occur over a typical playing career in collegiate American football players. In this prospective longitudinal study, we evaluated American football players (n = 48) in an academic institution affiliated with the National Collegiate Athletic Association Division I athletic program. Players underwent comprehensive ultrasonography of both knees prior to beginning their collegiate careers. Anatomic structures were evaluated for presence and severity of abnormalities. Noncontact lower extremity injuries sustained over the collegiate career of the subjects were documented. Data were analyzed for correlations, differences in proportions, and odds ratio (OR). Seventy-nine percent of the athletes had at least one ultrasonographic abnormality, with quadriceps tendon (47.9%) and patellar tendon (39.6%) abnormalities predominating. Seventy-nine percent of players had at least one noncontact lower extremity injury (23.5% involving the knee) during their careers with an average of 2.8 injuries per career. The majority of injuries occurred in the second and third playing years. There was a significantly higher likelihood of patellar tendon injury based on the presence of patellar tendon ultrasonographic pathology (p = 0.024; OR = 11x). There was a significantly higher likelihood of quadriceps muscle–tendon injury based on the presence of quadriceps tendon ultrasonography pathology (p = 0.0012; OR = 140x). All athletes sustaining meniscal injuries had preexisting joint effusion but no preexisting ultrasonographic meniscal pathology. Knee ultrasonography along with patient history and complete physical examination may help reduce injury risk through education, prevention, and training programs.
Keywords: collegiate American football; noncontact knee injuries; meniscal pathology; ultrasonography; medical screening